Предмет: Математика,
автор: sashanik126
1) ³√3х-1=2
2) √х+5=√12+х-1
Приложения:
Ответы
Автор ответа:
0
∛(3х-1)=2
3х-1=2³
3х-1=8
3х=9
х=3
А в этом во втором корне должен быть минус
√(х+5)=√(12-х-1)
х+5=12-х-1
х+х=11-5
2х=6
х=6 : 2
х=3
3х-1=2³
3х-1=8
3х=9
х=3
А в этом во втором корне должен быть минус
√(х+5)=√(12-х-1)
х+5=12-х-1
х+х=11-5
2х=6
х=6 : 2
х=3
Похожие вопросы
Предмет: Немецкий язык,
автор: fedunushunsofia30
Предмет: Математика,
автор: artemka22838
Предмет: История,
автор: valeriast2007
Предмет: Математика,
автор: Аноним